Irradiation level related to intraoperative imaging device in paediatric elastic stable intramedullary nailing: Preliminary prospective study on 51 patients using PCXMC software. (October 2020) - Prod'homme, Marc; Docquier, Pierre-Louis; Miri, Othmane; Sans-Merce, Marta; Tabard-Fougère, Anne; Ceroni, Dimitri; Lascombes, Pierre
Abstract: Purpose: Radiation-induced cancers due to imaging devices concern above all the growing child, however, to date, intraoperative irradiation doses are not well-documented in children. The goal of the study was to evaluate the intraoperative doses received by patients operated with the use of a C-arm in traumatology, as well as the lifetime attributable risk of cancer death (LAR) related to the irradiation of the imaging device. Methods: From 1 April 2017 to 31 March 2019, we started a multicentre study and prospectively recruited all consecutive children who needed elastic stable intramedullary nailing (ESIN) for long-bone fracture. We collected demographic and operative data, with dose reports including duration and doses. The main outcome was the effective dose (ED) in millisievert (mSv), calculated with PCXMC software, and the secondary outcome was the LAR expressed as a percentage. Results: In all, 51 patients operated on using 2D C-arm imaging were included in this study. The mean ED was 0.085 mSv (sd 0.10; 0.002 to 0.649). Overall LAR was 6.5 x 10 −4 % (sd 6.7 x 10 −4 %; 0.1 x 10 −4 % to 28.3x10 −4 %). Univariate linear regression showed a significant association between ED and irradiation time (p < 0.001). There was no significant association between ED and other outcomes (p > 0.05). Conclusion: Treatment of long-bone fractures by ESIN found a low level of effective doses with utilization of the C-arm device in current practice. Further studies on a larger sample are needed to confirm these results. Level of Evidence: II